Six-membered metalla-coronands. synthesis and crystal packing: columns, compartments, and 3D-networks. - Heinemann, Frank Wilhelm; et al. (Inorganic Chemistry, 2004)
Reaction of various N-substituted diethanolamines H(2)L(3) (4) with calcium hydride and iron(III) chloride leads to the self-assembly of six-membered ferric wheels [Fe(6)X(6)(L(3))(6)] (5). Principally, all the iron coronands are isostructural; however, they differ fundamentally with respect to their crystal packing. Exemplarily, this is discussed for selected members of the space groups R, P, P2(1)/c, P2(1)/n, C2/c, and P. Depending on the nature of their sidearms, the ferric wheels create various substructures. For instance, the ferric wheels 5a-i of space group R or P are piled in parallel in cylindrical columns, which are surrounded by six parallel columns alternately dislocated by (1)/(3)c and (2)/(3)c against the central one. Pronounced van der Waals interactions give rise to compartmentation and incarceration of guest molecules as seen for 5e,g. However, in 5h strong pi-pi interactions create a three-dimensional scaffold. The most significant difference of the ferric wheels 5j-p of space groups P2(1)/c, P2(1)/n, and C2/c is that these ferric wheels are arranged in parallel in two orientations. They differ mainly only by the included angle of the two groups of parallel wheels. In the case of 5l, molecular chains are formed in the crystal due to pi-pi interactions. The ferric wheels 5q-y of space group P are packed in the crystal most simply, with all the ferric wheels piled in parallel.